Microalgal CO2 sequestering – Modeling microalgae production costs - Bilanovic, Dragoljub; Holland, Mark; Armon, Robert (Energy conversion and management, 2012)
► Microalgae production costs were modeled as a function of specific expenses. ► The effects of uncontrollable expenses/factors were incorporated into the model. ► Modeled microalgae production costs were in the range $102–1503t−1ha−1y−1. Microalgae CO2 sequestering facilities might become an industrial reality if microalgae biomass could be produced at cost below $500.00t−1. We develop a model for estimation of total production costs of microalgae as a function of known production-specific expenses, and incorporate into the model the effects of uncontrollable factors which affect known production-specific expenses. Random fluctuations were intentionally incorporated into the model, consequently into generated cost/technology scenarios, because each and every logically interconnected equipment/operation that is used in design/construction/operation/maintenance of a production process is inevitably subject to random cost/price fluctuations which can neither be eliminated nor a priori controlled. A total of 152 costs/technology scenarios were evaluated to find 44 scenarios in which predicted total production costs of microalgae (PTPCM) was in the range $200–500t−1ha−1y−1. An additional 24 scenarios were found with PTCPM in the range of $102–200t−1ha−1y−1. These findings suggest that microalgae CO2 sequestering and the production of commercial compounds from microalgal biomass can be economically viable venture even today when microalgae production technology is still far from its optimum.